Trepanation in Italy: A Review. (7th June 2017) - Giuffra, V.; Fornaciari, G.
Abstract: This paper reviews and discusses cases of skull trepanation in ancient Italy on the basis of information provided by the literature. A total of 54 individuals from 43 different Italian archaeological sites were found to have evidence of trepanation. The analysis of evidences of trepanation in Italy has demonstrated that no differences can generally be perceived between the trepanned individual and the social context of the burial, leading to exclude a special role of the former within the group. Trepanation in Italy covers a time span of approximately 7000 years, the most ancient cases dating back to the fifth millenniumbc and the most recent to the 18th–19th centuriesad . The geographic distribution appears quite homogeneous, with a prevalence of cases in Central Italy and abundant evidence from prehistoric Sardinia. The majority of individuals show a single trepanation, whereas others present skulls with multiple holes. Trepanation in Italy was reserved to adult individuals, except for some rare cases, and shows a relevant preponderance for the male sex. The most diffused technique is scraping; cutting and drilling are less attested, especially as unique techniques for trepanation, but they were used more frequently in combination with scraping. Trepanation could in some cases be hypothesised as therapeutic intervention for the treatment of a traumatic wound or of other pathologies, whereas in other cases, a number of evidences are attested of trepanation performed as probable ritual intervention or as experimental surgery; in the remaining cases, the reasons for trepanation are unclear or not determinable. A high percentage of long‐term healing associated with trepanation has been evidenced. Copyright © 2017 John Wiley & Sons, Ltd.